الإشاریات ومقاصدها التداولیة في أشعار الشاعر الفلسطیني ولید سیف - غافلی, جمال; خضری , علی; بلاوی, رسول; پورعابد, محمد جواد; زارع, ناصر (University of Eloued جامعة الوادي, 2024)
تعمل التداولیة علی دراسة اللّغة في الاستعمال، حیث تُعنی بأنظمة التواصل بین مستعملي اللّغة، التي بدورها تعدّ نظاماً للتواصل الإنساني، فبواسطتها یُعبّر المتکلم عن الأفکار التي یرید تبلیغها للمخاطب. ولعلّ من أبرز مباحث الدَّرس التداولي: الإشاریات، کونها تعمل أساساً علی ربط علاقات عناصرها بمرجعیاتها اللّغویة والسیاقیة. الإشاریات عنصرٌ من عناصر التداولیة، ویُشار بها إلی ذات، أو زمان، أو مکانٍ؛ یأتي بها المشیرُ للکشفِ عن عناصر النصِّ من أشخاص، أو أماکن، أو أزمنة، أو أحداث وقعت بین الأطراف المشترکة في النص الخطابي، حیث تقوم بتوضیح المقصدیة من خلال سیاق النص. یعمد هذا البحث إلی دراسة أنواع الإشاریات؛الإشاریات الشخصیة، والزمانیة، والمکانیة، والاجتماعیة، ومقاصدها التداولیة في أشعار ولید سیف، اعتماداً علی المهنج الوصفي- التحلیلي. ولأهمیة الإشاریات في الخطاب الأدبي قدیماً وحدیثاً، لها نصیب وافر في أشعار ولید سیف، لذا أخذت مأخذاً واسعاً في دواوینه الشعریة، واستعمل الشاعر فیها مختلف ضمائر الخطاب، وأسماء الإشارة التي تدلُّ علی المکان، والزمان، والأشخاص. وانتهی البحث إلی مجموعة من النتائج أهمها أن طبیعة الدلالة المبهمة للإشاریات في المستوی اللساني تحتم علینا فهم إمکانیاتها الدلالیة المقصوده وغیر المقصودة في المستوی الاستعمالي؛ لتحدید الخرق الدلالي لکل إشاریة، والکشف عما یساعد في إیضاحها في الاستعمال، إضافة إلی أن للإشاریات قیمة خطابیة إنجازیة مثلها مثل بقیة المفاهیم التداولیة. Pragmatics studies language in use, as it is concerned with communication systems between language users, which in turn is a system for human communication, through which the speaker expresses the ideas that he wants to convey to the addressee. Perhaps one of the most prominent topics in the pragmatics lesson is deictic signs, as they basically work to link the relationships of its elements to their linguistic and contextual references. Deictic signs are an element of pragmatics, and they refer to a subject, a time, or a place that the signifier brings to reveal the elements of the text, whether people, places, times, or Events that occurred between the parties involved in the discursive text, which clarify the intention through the context of the text. This research intends to study the types of personal, temporal, spatial and social indicatives and their pragmatic purposes in Walid Saif’s poetry, based on the descriptive and analytical approach. Due to the importance of deictic letters in literary discourse, ancient and modern, they had a large share in Walid Saif’s poetry, so they took a wide role in his poetry collections, and the poet used in them various pronouns of speech, and demonstrative nouns that indicate place, time, and people. The research concluded with a set of results, the most important of which is that the ambiguous nature of the signs at the linguistic level requires us to understand their intended and unintended semantic possibilities at the usage level. To determine the semantic violation of each indicative, and to reveal what helps clarify it in use, in addition to the fact that indicatives have an accomplished rhetorical value like the rest of the concepts.
التداولیة، الإشاریات، السیاق، الشعر العربي المعاصر، ولید سیف